Characterization of osteoarthritic human knees indicates potential sex differences. Issue 1 (December 2016) - Pan, Qingfen; O'Connor, Mary; Coutts, Richard; Hyzy, Sharon; Olivares-Navarrete, Rene; Schwartz, Zvi; Boyan, Barbara
Abstract Background The prevalence of osteoarthritis is higher in women than in men in every age group, and overall prevalence increases with advancing age. Sex-specific differences in the properties of osteoarthritic joint tissues may permit the development of sex-specific therapies. Sex hormones regulate cartilage and bone development and homeostasis in a sex-dependent manner. Recent in vitro studies show that the vitamin D3 metabolite 1α, 25-dihydroxyvitamin D3 [1α, 25(OH)2 D3 ] also has sex-specific effects on musculoskeletal cells, suggesting that vitamin D3 metabolites may play a role in osteoarthritis-related sex-specific differences. The purpose of this study was to determine if sex-specific differences exist in synovial fluid and knee tissues isolated from male and female patients with severe knee osteoarthritis. We determined the presence of vitamin D3 metabolites, inflammatory cytokines, growth factors, and matrix metalloproteinases (MMPs) in synovial fluid and assessed responses of articular chondrocytes and subchondral osteoblasts to 17β-estradiol, dihydrotestosterone, and 1α, 25(OH)2 D3 . Methods Samples from knee joints of 10 Caucasian male and 10 Caucasian female patients with advanced osteoarthritis aged 65 to 75 years were obtained from total knee arthroplasty. Vitamin D metabolites, cytokines, MMPs, and growth factors in the synovial fluid were measured. Primary cultures of chondrocytes were isolated from fibrillated articular cartilage adjacent to osteoarthritis lesions and minimally affected cartilage distal to the lesion. Osteoblasts were isolated from the subchondral bone. Expression of receptors for 17β-estradiol and 1α, 25(OH)2 D3 was assessed by real-time PCR. Chondrocytes and osteoblasts were treated with 10−8 M 17β-estradiol, dihydrotestosterone, or 1α, 25(OH)2 D3 and effects on gene expression and protein synthesis determined. Results Histology of the articular cartilage confirmed advanced osteoarthritis. Sex differences were found in synovial fluid levels of vitamin D metabolites, cytokines, and metalloproteinases as well as in the cellular expression of receptors for 17β-estradiol and 1α, 25(OH)2 D3 . Male cells were more responsive to 1α, 25(OH)2 D3 and dihydrotestosterone, whereas 17β-estradiol-affected female cells. Conclusions These results demonstrate that there are underlying sex differences in knee tissues affected by osteoarthritis. Our findings do not address osteoarthritis etiology but have implications for different prevention methods and treatments for men and women. Further research is needed to better understand these sex-based differences.